Increased 10-year cardiovascular disease risk in depressed patients with coexisting subclinical hypothyroidism - Zhao, Shuai; Zhang, Boyu; Han, Yuqin; Guan, Jianjun; Fang, Wenmei; Zhang, Hongqin; Wang, Anzhen (Frontiers in Psychiatry, 2023)
Purpose The prevalence of depressive disorder (DD) and subclinical hypothyroidism (SH) was almost twofold higher in women compared with men, both of which are confirmed to be related to cardiovascular disease (CVD) risk. The current study aimed to identify the prevalence of CVD risk factors and evaluate the 10-year CVD risk in female depressed patients with and without comorbid SH. Methods We recruited 1744 female inpatients with a diagnosis of DD. Venous blood samples were taken from all patients for lipid and thyroid hormones. Framingham Risk Score (FRS) was used to estimate the 10-year CVD risk. Results Female depressed patients with SH had increased BMI, higher Hamilton Anxiety Scale (HAMA) scores, higher LDL-C, TC, UA, and a higher 10-year CVD risk than euthyroid DD groups. Serum TSH levels and HAMA scores were critical predictive variables for 10-year CVD risk in female depressed patients with comorbid SH. Conclusion Our study suggests that female depressed patients with SH have a high 10-year CVD risk. Serum TSH levels and HAMA scores may be helpful to predict cardiovascular risk in female patients with SH. The increased CVD risk in female depressed patients with comorbid SH requires more attention from researchers and clinicians.